Prevalence and determinants of parental refusal of human papillomavirus vaccination in Morocco: A multicenter cross-sectional study - Touria Essayagh; Meriem Essayagh; Kaoutar Nmila; Housnia Slibani; Soukayna El Hachimi; Mustapha El Boukhari; Hajar Lemriss; Sanaâ Lemriss; Rehmatullah Zadran; Halima Tigaidi; Sanah Essayagh (PLoS ONE, 2026)
Introduction Vaccination against the human papillomavirus (HPV) is an effective way to avert cervical cancer. However, acceptance in Morocco remains inadequate. The aim of this study was to measure the prevalence of parental HPV vaccine refusal and the risk factors associated with it. Methods Between 3 March and 30 September 2025, a multicenter cross-sectional survey was conducted among Moroccan parents of girls aged 11–14 who attended health facilities. The study looked at sociodemographic factors, knowledge regarding HPV and cervical cancer, and vaccination attitudes. A multivariate logistic regression analysis was used to identify risk factors for vaccination refusal. Results The research included 1,444 participants with an average age of 37.7 ± 6.6 years. Of them, 415 refused HPV vaccination for their daughters, resulting in a prevalence of 28.7%. Vaccine refusal was substantially related to higher educational levels, lower income, less faith in the healthcare system, less knowledge about cervical cancer and its symptoms, and insufficient information regarding the HPV vaccine as seen by the media. Refusal was also associated with a poor perception of the seriousness of HPV infection, fear of vaccinating daughters, noncompliance with past vaccination schedules, difficulties accessing health centers, and a lack of recommendations from healthcare professionals. In contrast, refusal was inversely associated with parents who were uninformed of the proper number of vaccination doses or uninformed regarding the availability of the HPV vaccine at health centers or who feared the vaccine may cause an adverse reaction. Conclusion Parental refusal of HPV vaccination is still a substantial obstacle. To increase acceptability and enhance cervical cancer prevention in Morocco, it is critical to expand communication strategy, boost public knowledge, and assure active participation of healthcare professionals.